WHI-2 Regulates Intercellular Communication via a MAP Kinase Signaling Complex - Gonçalves, A. Pedro; Chow, Karen M.; Cea-Sánchez, Sara; Glass, N. Louise (Frontiers in Microbiology, 2020)
The formation of the fungal mycelial network is facilitated by somatic cell fusion of germinating asexual spores (or germlings). Neurospora crassa germlings in close proximity display chemotropic growth that is dependent upon an intracellular network of mitogen-activated protein kinase (MAPK) signaling cascades. Approximately 80 genes involved in intercellular communication and fusion have been identified, including three mutants with similar morphological phenotypes: ∆whi-2, ∆csp-6 and ∆amph-1. Here we show that WHI-2 localizes to the cell periphery and regulates endocytosis, mitochondrial organization, sporulation and cell fusion. WHI-2 was required to transduce signals through a conserved MAPK pathway (NRC-1/MEK-2/MAK-2) and target transcription factors (PP-1/ADV-1). The amph-1 locus encodes a Bin/Amphiphysin/Rvs domain-containing protein and mis-expression of whi-2 compensated for the cell fusion and endocytosis deficiencies of a ∆amph-1 mutant. The csp-6 locus encodes a haloacid dehalogenase phosphatase whose activity was essential for cell fusion. Although fusion-deficient with themselves, cells that lacked whi-2, csp-6 or amph-1 showed a low frequency of chemotropic interactions with wild type cells. We hypothesize that WHI-2 could be important for signal perception during chemotropic interactions via a role in endocytosis.